Implementasi Model Problem Based Learning (PBL) dalam Meningkatkan Kemampuan Berpikir Kritis Mahasiswa melalui Lesson Study - Aziz, Abdul; Ahyan, Shahibul; Fauzi, Lalu Muhammad (Universitas Hamzanwadi, 2016)
This study aims to describe the implementation of problem based learning model to improve critical thinking skills of students in the subjects of Mathematics of Economics V semester of the academic year 2015/2016. This type of research used in this study is the Classroom Action Research (CAR through Lesson Study activities which consists of three stages; plang, do and see. Data collection techniques used are tests, questionnaires, observation, field notes and documentation. The data analysis technique used is descriptive qualitative. The results showed that the classification of critical thinking skills of students in the first and second open class is quite good with a percentage of 67.33% and 68.56%. In the third and fourth open class, critical thinking abilities of students has increased with the percentage of 74.22% and 77.78% with the classification of critical thinking is good. Therefore, the critical thinking skills of students in the subject of Mathematics of Economics can be improved by using problem-based learning through lesson study.